The Effect of Compensation and Competence on Performance with Motivation as a Variable Intervening an Employee in Partners of the Central Statistic Agency, Lubuklinggau City, South Sumatra, Indonesia - Susanto, Yohanes; Oktovianus, Farid; Habaora, Fellyanus; Riwukore, Jefirstson Richset (International Business Management - Universitas Ciputra, 2021)
The purpose of this research was to determine the effect of compensation and competence on performance with motivation as a variable intervening an employee. The research has been conducted for 6 months, namely June to December 2019 at the Central Bureau of Statistics of Kota Lubuklinggau, South Sumatra Province, Indonesia. The population in this research were 133 respondents. This research is explanatory research using primary data and secondary data. Primary data collection methods use interview techniques and questionnaires, in addition to conducting field observations. Secondary data were collected using documentation techniques. The data analysis uses the statistical analysis of the Structural Equation Model (SEM) based on predetermined hypotheses including compensation, competence, and motivation which partially or jointly affect the performance of partners at the Central Bureau of Statistics Office in Kota Lubuklinggau. The results showed that the aspects of compensation and competence at the Office of the Central Bureau of Statistics in Kota Lubuklinggau have not been fulfilled optimally. Partially, there is a positive and significant relationship between compensation toward motivation, competence toward performance, compensation and competence toward performance, but there is no positive and significant effect between compensation toward performance, motivation toward performance, as well as compensation-competence-motivation together toward performance, and there is also a positive but not significant influence between competence toward motivation. The results of this research indicate that there needs to be an improvement in competence and compensation from the Office of the Central Bureau of Statistics of Kota Lubuklinggau to its partners.